« Hair-oes » et « hair-oines » : les choix capillaires osés de John Neal, ou comment circonscrire l’Américain, entre poil dur et poil souple - Sébastien Liagre (Transatlantica)
This paper explores the quasi-obsessional use John Neal (1793-1876) makes of hair: the vibrating nealian hair is a neutral ground, a ground where the alchemy shaping Neal’s androgynous American is at work. This study offers a new perspective on the “Declaration of Independence, in the great Republic of Letters” proclaimed in the preface of Rachel Dyer (1828): following Neal’s wavy-haired protagonists, we come closer to the heart of his “Frontier-writing,” American, though underrated.